Regulation of Auxin-induced Ethylene Production in Mung Bean Hypocotyls: Role of 1-Aminocyclopropane-1-Carboxylic Acid - Yu, Yeong-Biau (1979)
Ethylene production in mung bean hypocotyls was greatly increased by treatment with 1-aminocyclopropane-1-carboxylic acid (ACC), which was utilized as the ethylene precursor. Unlike auxin-stimulated ethylene production, ACC-dependent ethylene production was not inhibited by aminoethoxyvinylglycine, which is known to inhibit the conversion of S-adenosylmethionine to ACC. While the conversion of methionine to ethylene requires induction by auxin, the conversion of methionine to S-adenosylmethionine and the conversion of ACC to ethylene do not. It is proposed that the conversion of S-adenosylmethionine to ACC is the rate-limiting step in the biosynthesis of ethylene, and that auxin stimulates ethylene production by inducing the synthesis of the enzyme involved in this reaction.